Differential scattering cross sections for electron scattering by ytterbium atom - Pandya, C. V. (Array, 2009)
Electron scattering by ytterbium atom is studied at energies 10, 20, 40, 60 and 80 eV, by applying a parameter-free complex optical potential. The real part of the complex optical potential includes the static potential Vst(r), the polarization potential Vpol(r) that consists of the short range correlation and long-range polarization effects and Vex(r) term consisting of electron exchange interaction which is modelled by assuming the electron charge cloud as a free electron gas. The loss of flux into the inelastic channels is included via a phenomenological absorption potential. Our results are compared with the recent experimental measurements